ANALISIS PENGARUH STABILISASI TANAH DENGAN PASIR SUNGAI SANGATTA TERHADAP UJI GESER DAN CBR - NUR SYARIF, HANDRA (KURVA S JURNAL MAHASISWA, 2014)
Â  In this research will be used in the additive in the form of sand obtainedfrom sand rivers, to find out in the addition of sand creek stabilization Sangattaobtained the original soil shear strength valueswhen added stabilistator. The sandwas obtained directly from the bottom of the river is generally fine-grained round-round process because of friction.The ground has very loose,and have a consistency index do not fit as well asa high permebilitas of unwanted approaches , by processing it is necessary becausethe back so that it could be used as the supporter of the construction, namely bymeans of stabilization.Comparisonof the results obtained as follows:With the use of the land 75% plus the use of sand 25% obtained the value ofcohesion(c)( 0.446 Kg/Cm2), shear strenght (S)( 12.572) Kg/Cm2, and max valuesof CBR100% (6.400%).With the use of the land 70% plus the use of sand 30% obtained the value ofcohesion(c)( 0.422 Kg/Cm2), shear strenght (S)( 9.524) Kg/Cm2, and max values ofCBR 100% (4.300%).With the use of the land 100% then obtained the value of cohesion(c)( 0.686Kg/Cm2), shear strenght (S)( 24.861) Kg/Cm2, and max values of CBR 100%(8.100%).So the larger the contents of the water levels will decrease the value ofcohesion(C),shear angle value in the zoom(Ï‰)as well as enlarge strong shearstrength. So in addition to this sand stabilization material should not be more than30% because it can shift.